Multifunctional Scaffolds with Improved Antimicrobial Properties and Osteogenicity Based on Piezoelectric Electrospun Fibers Decorated with Bioactive Composite Microcapsules; ACS Applied Materials & Interfaces; Vol. 41, iss. 10 - Timin A. S. Aleksandr Sergeevich; Muslimov A. R. Albert Radikovich; Zyuzin M. V. Mikhail; Peltek A. O. Aleksey Olekseevich; Karpov T. E. Timofey Evgenjevich; Sergeev I. S. Igor Sergeevich; Doshchenko A. I. Anna Igorevna; Goncharenko A. A.; Yuylshin N. S. Nikita Sergeevich; Sinelnik A. Artem; Krauze B. Barbel; Baumbach T. Tilo; et al. (2018, 2018)
Title screen